Mapeamento dos processos de licenciamento ambiental de atividades petrolíferas onshore do RN - Lima, Camila Silva (Universidade Federal Rural do Semi-Árido, 2021)
The Brazilian public service that has been undergoing constant transformations, seeking service efficiency, decentralizing attributions and thus demystifying the rigid organizational structure, which was considered delicate, time-consuming, complex and very bureaucratic processes. Thus, there is a need for the environmental licensing processes of the Institute for Development and Environment – IMA to be increasingly structured and organized, aiming at opportunities for improvement of different types of processes. The objective of this work was to map and explain the tacit knowledge related to the licensing process, as well as to identify the licensing processes, in addition to analyzing the flows of the necessary internal processes and graphically and systematically represent the licensing process (Model "As is") at IDEMA's Center for Analysis and Licensing of Petroleum Activities. A bibliographical research was carried out concerning works related to processes, organizational process management, knowledge management, methodology and support tools for process modeling. Data collection was carried out by consulting technicians and the coordinator of the analyzed sector, considering the knowledge and experience of the servers in the licensing processes. With the application of concepts on Business Process Modeling Notation (BPMN) it was possible to identify the processes to be mapped and relate them to the types of enterprise subject to licensing. It was concluded that the flow of licensing processes is the same for all identified processes. It was also possible to map the process for environmental licensing. Finally, opportunities for improvement in the current mapped process were presented and suggestions for future work were presented
Keywords: Gestão de Processos; Serviço Público; Gestão do Conhecimento; Process Management; Public service; Knowledge Management; ENGENHARIAS::ENGENHARIA DE PRODUCAO